دور الأنشطة اللاصفية في تحقيق التكيف المدرسي لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة - خديجة قرميط; بورقعة نبيلة (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى الكشف عن دور الأنشطة اللاصفية في تحقيق التكيف المدرسي لدى تلاميذ الابتدائي من وجهة نظر المعلمين. حيث أجريت الدراسة على عينة متكونة من 100 معلم من خمس إبتدئيات. وتم الاعتماد على المنهج الوصفي الارتباطي، وهو أحد فروع المنهج الوصفي. ومن أجل دراسة الموضوع اعتمدنا على الاستبيان تناول دور الانشطة اللاصفية في تحقيق التكيف المدرسي والمكون من 30 بند وتم التحقق من الخصائص السيكومترية للأداة (الصدق والثبات) وبعدها توزيعه على أفراد العينة واسترجاع كل الاستمارات الموزعة وتم تحليل النتائج باستعمال برنامج spss وبرنامج excel. وبعد المعالجة الإحصائية للنتائج المتحصل عليها توصلت الدراسة إلى أن الانشطة اللاصفية قد ساهمت بدرجة كبيرة في تحقيق التكيف النفسي والاجتماعي والدراسي لدى تلاميذ الابتدائي من وجهة نظر الأساتذة وهذا ما بينته بنود الاستبيان. " The study aimed to reveal the role of extracurricular activities in achieving school adjustment among primary school pupils from the teachers’ perspective. The study was conducted on a sample of 100 teachers from five primary schools. The descriptive correlational method, which is a branch of the descriptive method, was adopted. To investigate the topic, a questionnaire was used that addressed the role of extracurricular activities in achieving school adjustment. The questionnaire consisted of 30 items, and its psychometric properties (validity and reliability) were verified. Afterwards, it was distributed to the sample members, and all distributed forms were collected. The data were analyzed using SPSS and Excel software. After the statistical analysis of the obtained results, the study concluded that extracurricular activities significantly contributed to achieving psychological, social, and academic adjustment among primary school pupils from the teachers’ point of view, as demonstrated by the questionnaire items. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: التكيف المدرسي; الأنشطة اللاصفية; المدرسة; التكيف; Adjustment; School; Extracurricular Activities; School Adjustment